Sosialisasi Social Media Marketing untuk Meningkatkan Pemasaran Yayasan Al-Birru Indonesia Jaya - Safitri, Rizky Ade; Prakoso, Bobby Suryo; Prasetyo, Johan Hendri; Fabrianto, Luky; Wiharso, Gani; Nabilah, Saripah; Yuwanda, Henny; Abdullah, Hamzah Ali; Afriano, Daniel Chandra; Febrianti, Nurlia (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2022)
Covid-19 has become a world frightening global pandemic in humans history including in Indonesia. This resulted in large-scale social restrictions that have an impact to all business sectors in Indonesia, including the Al-Birru Indonesia Jaya Foundation, which is a non-profit organization at Bekasi. Therefore, it is necessary to use social media in order to increase the marketing of Al-Birru Indonesia Jaya Foundation so that it will continue to exist and help the orphans and poor people to get better education. According to these reasons background, Universitas Nusa Mandiri held a socialization through social media marketing to increase the marketing of the Al-Birru Indonesia Jaya Foundation. The types of outputs produced from this community service activity are in the form of press releases in electronic print media, and documentation in the form of photos of community service itself. The purpose from this socialization are to introduce Facebook-Ads and Instagram-Ads applications as marketing media and convey appropriate strategies to increase the marketing of the Al-Birru Indonesia Jaya Foundation so that it would get better known in the public and also would have an impact to the income of the Al-Birru Indonesia Jaya Foundation in an efforts to help orphans and poor people get a better education. The result of this socialization is to improved the knowledge and understanding from the participants relates to on how to use social media marketing properly and appropriately with hopes to improve the marketing of the Foundation so it would get better known by the wider community